M&A advisory process in Bangladesh- a case study on the foreign acquisition of a FMCG Company - Mim, Nishat Afnan (BRAC University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.